A mobile application for streamlining job search for people with disabilities / Muhammad Ammar Redza … [et al.] - Redza, Muhammad Ammar; Mohd Selan, Muhammad Ezhan Shafri; Mohd Azmi, Rabiatul Adawiyah; Sanusi, Noor Aina Batrisyia; Ridzuan, Zarifah; Kassim, Suhailah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The project aims to create a user-friendly mobile application for job search for people with disabilities, addressing the challenges faced by disabled individuals in finding meaningful work. The main objectives include developing an accessible interface, building a database of disability-friendly companies, and simplifying the job application process with tools like resume builders, communication tools, and customizable profiles. The mobile application emphasizes inclusivity and accessibility during the job search process, integrating adaptive design concepts and addressing the unique needs of individuals with disabilities. Its potential impact includes enabling disabled individuals to actively participate in the labor market, fostering connections between job seekers and employers who accept disabilities, and creating a more inclusive society. The application has the potential for commercialization, offering premium services or subscription plans, collaborating with job search platforms to incorporate accessibility features, and cooperating with disability advocacy organizations for financing and support. Advertisement partnerships and sponsored content catering to user interests could also generate income. In conclusion, developing a mobile application for job searchers with impairments is a crucial step towards workplace inclusion, and promoting equality and diversity. It is beneficial to both people and companies, and its success depends on continued cooperation and dedication to accessibility.